Hearing impairment screening in adults with chronic general somatic pathology in the republic of Adygeya - L. A. Lazareva; S. A. Azamatova; A. G. Kekeliya; E. V. Zhugan; L. V. Tsyplenkov; B. R. Muzaeva; I. S. Elizbaryan (Кубанский научный медицинский вестник, 2020)
Background. The steadily growing number of hearing-impaired patients incited epidemiological research into the etiopathogenesis of sensorineural hearing loss.Objectives. To conduct a screening survey of hearing-impaired adults to identify early sensorineural hearing loss in patients with chronic general somatic pathology in the Republic of Adygea.Мethods. We used a screening method for auditory function disorder diagnosis based on surveying patients with no primary hearing complaints. A total of 6,346 patients with variant chronic general somatic pathology were surveyed anonymously. Statistical analysis and interpretation were performed with Statistica 10.0 and MS Excel 2010.Results. A point–based assessment survey of the patient’s psycho-emotional state in various classroom settings identifi ed the sensorineural disorder risk groups among the visitors of district and municipal outpatient units. Subclinical auditory function disorders were revealed in 16.5% (1045 of 6346), and putative hearing loss of various degree — in 36.2% (2295 of 6346) of the patients. In 47.3% (3006 of 6346), no evidence of hearing loss was observed in the survey. Accentuated analysis revealed early and severe hearing disorders among patients with cardiovascular, endocrine, nervous, excretory, respiratory and other diseases.Conclusion. We show the applicability of screening surveys for detecting early sensorineural hearing loss in patients with chronic general somatic pathology. Acceptance of adapted surveying by family physicians, neurologists and adult endocrinologists will facilitate preclinical identifi cation of risk groups among patients requiring specialised audiological care.